2018
DOI: 10.5897/ajar2018.13207
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea response to nutrient application in Burkina Faso and Niger

Abstract: Cowpea (Vigna unguiculata (L.) Walp) is important in semi-arid West Africa. Yields are low due to inadequate water and nutrient availability and other constraints. Grain and fodder yield responses to nutrient application were determined from 21 site-years of research conducted in the Sahel and Sudan Savanna. The incomplete factorial treatment arrangement varied by country but included: Four levels each of P and K in 7.5 and 10.0 kg ha -1 increments, respectively; Mg-S-Zn-B package (Mg-S-Zn-B); and comparable w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…The ZT (503.6 Kgha -1 ), ST (338.8 Kgha -1 ) and DT (464.3 Kgha -1 ) were all statistically insignificant. This conforms with the findings of a number of studies (Idriss et al, 2018;Mando & Vanlauwe, 2005;Meena et al, 2015). The interaction was significant in such a way that the grain yield produced is higher at PM plots in a succession of ZT, ST then DT plots from Figure 6.…”
Section: Single Pod Weight (G)supporting
confidence: 91%
See 1 more Smart Citation
“…The ZT (503.6 Kgha -1 ), ST (338.8 Kgha -1 ) and DT (464.3 Kgha -1 ) were all statistically insignificant. This conforms with the findings of a number of studies (Idriss et al, 2018;Mando & Vanlauwe, 2005;Meena et al, 2015). The interaction was significant in such a way that the grain yield produced is higher at PM plots in a succession of ZT, ST then DT plots from Figure 6.…”
Section: Single Pod Weight (G)supporting
confidence: 91%
“…Tillage X OM was highly significant as depicted by Figure 5. (Idriss et al, 2018) reported a significant increase in cowpea performance in both Niger and Burkina Faso due to OM. Mando and Vanlauwe (2005) also reported a significant long term interaction between tillage and manure on general crop performance and soil properties improvement in the dry Sahelian regions of West Africa.…”
Section: Single Pod Weight (G)mentioning
confidence: 97%